Effects of vildagliptin (Galvus(R)) therapy in patients with type 2 diabetes mellitus after heart transplantation - Güler, Ibrahim; Müller, Susanne; Helmschrott, Matthias; Oeing, Christian; Erbel, Christian; Frankenstein, Lutz; Gleißner, Christian A.; Ruhparwar, Arjang; Ehlermann, Philipp; Dengler, Thomas; Katus, Hugo; Dösch, Andreas (Drug design, development and therapy, 2013)
Background - Type 2 Diabetes mellitus (T2DM) is a common comorbidity in patients after heart transplantation (HTx) and is associated with adverse long-term outcomes. - - Methods - The retrospective study reported here analyzed the effects of vildagliptin therapy in stable patients post-HTx with T2DM and compared these with control patients for matched-pairs analysis. A total of 30 stable patients post-HTx with T2DM were included in the study. Fifteen patients (mean age 58.6 ± 6.0 years, mean time post-HTx 4.9 ± 5.3 years, twelve male and three female) were included in the vildagliptin group (VG) and 15 patients were included in the control group (CG) (mean age 61.2 ± 8.3 years, mean time post-HTx 7.2 ± 6.6 years, all male). - - Results - Mean glycated hemoglobin (HbA1c) in the VG was 7.4% ± 0.7% before versus 6.8% ± 0.8% after 8 months of vildagliptin therapy (P = 0.002 vs baseline). In the CG, HbA1c was 7.0% ± 0.7% versus 7.3% ± 1.2% at follow-up (P = 0.21). Additionally, there was a significant reduction in mean blood glucose in the VG, from 165.0 ± 18.8 mg/dL to 147.9 ± 22.7 mg/dL (P = 0.002 vs baseline), whereas mean blood glucose increased slightly in the CG from 154.7 ± 19.7 mg/dL to 162.6 ± 35.0 mg/dL (P = 0.21). No statistically significant changes in body weight (from 83.3 ± 10.8 kg to 82.0 ± 10.9 kg, P = 0.20), total cholesterol (1.5%, P = 0.68), or triglyceride levels (8.0%, P = 0.65) were seen in the VG. No significant changes in immunosuppressive drug levels or dosages were observed in either group. - - Conclusion - Vildagliptin therapy significantly reduced HbA1c and mean blood glucose levels in post-HTx patients in this study with T2DM and did not have any negative effects on lipid profile or body weight. Thus, vildagliptin therapy presented an interesting therapeutic approach for this selected patient cohort.
Das Registered-Trade-Mark-Symbol ist in kleinerer Schriftgröße dargestellt und zwar als ein hochgestellter, eingekreister Großbuchstabe „R“, der hinter Galvus angefügt wird
Gesehen am 11.02.2021